Probiotics/synbiotics supplementation reduce the infection incidence in patients undergoing resection for colorectal cancer: an umbrella review - Gao, Shilin; Liao, Xi; He, Yuhua; Yang, Jie (Frontiers in Microbiology, 2025)
ObjectivesThis study reviews meta-analyses of perioperative supplementation with probiotics/synbiotics in colorectal cancer (CRC), systematically assessing the quality of meta-analyses and synthesizing study results to provide robust evidence.MethodsThis review was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. The search was conducted by two authors in four databases, PubMed, CENTRAL, EMBASE and Web of Science, up until August 3rd, 2025, and conducted independent assessments of the methodological quality of the meta-analysis via A Measure Tool to Assess Systematic Reviews (AMSTAR) 2.ResultsA total of 11 meta-analyses were included in this umbrella review. 3 meta-analyses rated “Critically low” shared ≥3 critical flaws and 2 high-rated reviews adhered to ≥80% AMSTAR 2 criteria. Compared with the control group, the probiotic/synbiotic group presented lower incidence rates of overall infections (OR 0.49, 95% CI: 0.43, 0.56; P < 0. 001, I2 = 6%), surgical site infections (OR 0.58, 95% CI: 0.50, 0.67; P < 0.00001, I2 = 0%), urinary tract infections (OR 0.39, 95% CI: 0.27, 0.54; P < 0.00001, I2 = 0%), and pneumonia infections (OR 0.34, 95% CI: 0.26, 0.45; P < 0.00001, I2 = 0%), and diarrhea incidence (OR 0.41, 95% CI: 0.34, 0.51; P < 0.00001, I2 = 0%).ConclusionAccording to the results of our analyses, perioperative probiotic/synbiotic supplementation in CRC patients is associated with a reduced incidence of overall infections, surgical site infections, urinary tract infections, pneumonia infections, and diarrhea.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024619853.